2006
DOI: 10.3354/cr032063
|View full text |Cite
|
Sign up to set email alerts
|

Influence of teleconnection patterns on precipitation variability and on river flow regimes in the Miño River basin (NW Iberian Peninsula)

Abstract: The influence of the most representative winter patterns of atmospheric variation in the Northern Hemisphere on precipitation variability and on river flow regimes was evaluated for the Miño River basin (NW Iberian Peninsula). The Arctic Oscillation (AO) was also considered in order to analyze the effect of a larger-scale atmospheric mode on precipitation and river flow. Precipitation data were obtained from 22 rain-gauge stations located within the Miño River basin from 1976 to 1997, and the Miño River flow d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 27 publications
0
34
0
1
Order By: Relevance
“…Other teleconnection patterns that appear in the Northern Hemisphere (Barnston and Livezey, 1987) are the Scandinavian Pattern (SCA), the Polar/Eurasia Pattern (POL), the EA, and the (EA/WR). The NAO is the most important one in our area, but the EA, EA/WR and SCA are also significant - Taboada, 2005 andDeCastro et al, 2006, found that winter rainfall in Galicia is explained mainly by four indices (NAO, EA, EA/WR and SCA). The influence of four different indices, three representing north-south dipoles and another representing an east-west dipole, means that Galicia is located in an area that is subject to a wide variety of influences (Figure 2).…”
Section: Relationship Between Synoptic Weather Types and Different Rementioning
confidence: 99%
See 2 more Smart Citations
“…Other teleconnection patterns that appear in the Northern Hemisphere (Barnston and Livezey, 1987) are the Scandinavian Pattern (SCA), the Polar/Eurasia Pattern (POL), the EA, and the (EA/WR). The NAO is the most important one in our area, but the EA, EA/WR and SCA are also significant - Taboada, 2005 andDeCastro et al, 2006, found that winter rainfall in Galicia is explained mainly by four indices (NAO, EA, EA/WR and SCA). The influence of four different indices, three representing north-south dipoles and another representing an east-west dipole, means that Galicia is located in an area that is subject to a wide variety of influences (Figure 2).…”
Section: Relationship Between Synoptic Weather Types and Different Rementioning
confidence: 99%
“…The storm track in this area depends strongly on the North Atlantic Oscillation (NAO) (Trigo, 2006). Other teleconnection patterns, such as the Scandinavian Pattern (SCA) or the Eastern Atlantic (EA) are also important for explaining variability in precipitation (Blackburn and Hoskins, 2001;Lorenzo and Taboada, 2005;DeCastro et al, 2006). It has been found that correlations between winter rainfall in Galicia and the NAO index have a value of −0.52, while correlations with other indices are lower, but significant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NAO influences wind intensity and direction, thus regulating quantities of precipitation over the North Atlantic (Hurrell 1995). The East Atlantic Pattern (EAP) index is similar to the NAO but relates to the subtropical area (Barnston & Livezey 1987, deCastro et al 2006). This index is an important element to consider because of its strong influence on the environment of western Europe and the French coast (Msadek & Frankignoul 2009).…”
Section: Hydro-climatic Datamentioning
confidence: 99%
“…Other teleconnection patterns appearing in the North Atlantic and also affecting climate variability over the IP are the Scandinavian (SCAND), Eastern Atlantic (EA), and Eastern Atlantic-Western Russia (EA-WR) patterns, which increases the complexity of climate-change studies. Thus, recent studies have proved that atmospheric and oceanic phenomena such as precipitation, river discharge, and upwelling should be explained in terms of >1 teleconnection pattern (Lorenzo & Taboada 2005, deCastro et al 2006a.…”
Section: Introductionmentioning
confidence: 99%